tính nhanh các biểu thức sau:
(84/13)^2 + ( 35/13)^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\frac{84}{13}\right)^2+\left(\frac{35}{13}\right)^2=\left(\frac{84^2+35^2}{13^2}\right)=\frac{7056+1225}{169}=\)\(49\)
\(=\left(87-13\right)\left(87+13\right)=74\cdot100=7400\)
Lời giải:
a. $=13-47-13-59+81+35-13$
$=(13-13-13)-(47+59)+(81+35)$
$=-13-106+116=-13+(116-106)=-13+10=-3$
b.
$=345-61+84+61-116-345$
$=(345-345)+(-61+61)-(116-84)$
$=0+0-32=-32$
\(=\left(\frac{84}{13}+\frac{35}{13}\right)^2-2\cdot\frac{84}{13}\cdot\frac{35}{13}\)
\(=7^2-\frac{5880}{169}\)
\(=49-\frac{5880}{169}\)
\(=\frac{8281}{169}-\frac{5880}{169}=\frac{2401}{169}\)
\(\left(\frac{84}{13}\right)^2+\left(\frac{35}{13}\right)^2=\left(\frac{84^2+35^2}{13^2}\right)=\frac{7056+1225}{169}=49\)
tự làm vậy